PENDIDIKAN KEWIRAUSAHAAN, OPPORTUNITY RECOGNITION DAN MINAT BERWIRAUSAHA DI INDUSTRI PARIWISATA HALAL - Sakti, Dwi Putra Buana; Nirwana, Baiq Nadia; Pratama, Rionaldi Gigih Imam; Prayanti, Yulia (Jurnal Magister Manajemen, 2020)
This study aims to provide an understanding of the factors forming youth entrepreneurial intention in the halal tourism industry. This research uses a quantitative method with a causality approach. Data was collected from university students in West Nusa Tenggara who have taken entrepreneurship courses. The results show that entrepreneurship education influences opportunity recognition and entrepreneurial intention in halal tourism industry, opportunity recognition influences entrepreneurial intention in halal tourism and entrepreneurship education influences entrepreneurial interest in halal tourism through opportunity recognition. The West Nusa Tenggara government and universities are suggested to develop a curriculum related to halal tourism and link existing courses with topics of halal tourism.